Cateterismo cardíaco de exercício na hipertensão arterial pulmonar idiopática: avaliação dos mecanismos hemodinâmicos fisiopatológicos associados ao consumo máximo de oxigênio - Messina, Carolina Montemor Soares [UNIFESP] (2018)
Introduction: Idiopathic pulmonary arterial hypertension (IPAH) is characterized by pulmonary vascular remodeling and an associated increased pulmonary vascular resistante (PVR), which over time, can lead to right ventricular (RV) dysfunction. IPAH´s exercise tolerance, clinical evolution and survival are known to be associated with the RV adaptation to its increased afterload. However, little is known regarding the specific hemodynamic mechanisms associated with a reduced aerobic capacity in patients with severe IPAH. Objectives: To evaluate the hemodynamic mechanisms associated with peak oxygen consumption (V̇ O2) during exercise in patients with IPAH; to describe the hemodynamic patterns during exercise right heart catheterization in IPAH; and to identify the hemodynamic predictors of peak V̇ O2. Methods: Twenty patients with IPAH from the Pulmonary Hypertension Outpatient Clinic of the Federal University of São Paulo between September 2014 and March 2016 were included in the current study. All patients were submitted to contemporary pulmonary functional test, a sixminute walk test, transthoracic echocardiography, cardiopulmonary exercise testing (CPET) and resting supine right heart catheterization (RHC) followed by exercise hemodynamic assessment. Results: 85% of the patients were female, with a median age of 34[2942] and 95% were New York Heart Association functional class (NYHAFC) II or III. During exercise right heart catheterization, peak work was 30[2030] W, peak mean pulmonary arterial pressure was 76 ± 17 mmHg, peak pulmonary arterial wedge pressure was 14 ± 5 mmHg, peak PVR was 959 ± 401 dynes.s.cm5. Peak cardiac output (CO) and the peak cardiac index (CI) were 5,7 ± 1,9 L/min and 3,5 ± 1,2 L/min/m2, respectively. Peak stroke volume index (SVI) was 29 ± 12 mL/m², peak right ventricular stroke work index (RVSWI) was 29 ± 14 g/m2/bat and peak pulmonary vascular compliance (PVC) was 0,9[0,61,2] ml/mmHg. There was a positive correlation between peak V̇ O2 and peak CO (r=0,528; p=0,017), peak CI (r=0,599; p=0,005), peak SVI (r=0,494; p=0,027), peak RVSWI (r=0,543; p=0,013) and peak peripheral oxygen saturation (peak SpO2) (r=0,408; p=0,074). There was a negative correlation between peak V̇ O2 and ΔPVC (r=0,409; p=0,073). By univariate analysis, peak CO, peak CI, peak SVI, peak RVSWI, ΔPVC and peak SpO2 were predictors of peak V̇ O2. By multivariate analysis adjusted for age, only peak RVSWI (Coefficient= 0,145, CI 95% [0,0720,2219], p=0,001) and ΔPVC (Coefficient=2,510, CI 95% [4,344( 0,677)], p=0,01) remained independent predictors of peak V̇ O2. Conclusions: In IPAH, increased peak RVSWI and decreased ΔPVC during exercise are associated with a reduced peak V̇ O2. Given that RVSWI and ΔPVC represent the RV contractility and its afterload, respectively, the study findings suggest that RVpulmonary arterial coupling determine maximal aerobic capacity in IPAH.